Design of Hydraulic Operated Clutch on Typical Motorcycle - Suyitno Suyitno (Automotive Experiences, 2019)
The mechanical operating clutch (threaded wire) on the motorcycle has been complained of having many disadvantages, including operational failure due to broken wire and heavy operating force. Therefore, this article reports the design of the hydraulic operating clutch mechanism on the Yamaha RX-King to replace mechanical systems. Modification is done by adding a master cylinder, fluid hose, release cylinder, and push rod. The calculation results show that the hydraulic operating clutch has the potential to reduce the operational force by up to 6x of mechanical clutch.